Kewirausahaan Politik Kepala Daerah: Studi Kasus Program Unggulan Panca “Pinter Rakyate” di Kabupaten Wonogiri - Tri Fauzia, Ofifah (Brawijaya University, 2024)
Political entrepreneurship is an effort by political actors in the form of leadership innovation to increase public interests as political entrepreneurs. In this research, the innovation created by the regional head, the Regent of Wonogiri, was in the form of the Panca